Paleomagnetism of diabase dikes from the Bonavista Bay area of northeastern central Newfoundland - Murthy, G. S. (Canadian Journal of Earth Sciences, 1983)
Paleomagnetic results are reported for a swarm of diabase dikes from the northeastern Gander Zone of the Newfoundland Appalachians. Sixty-eight cores were collected from 19 dikes cutting the various granites and migmatites from the Bonavista Bay area of Newfoundland. From the earlier structural and Rb/Sr age data available, one can infer an age for the dike swarm of between 400 and 330 Ma. Paleomagnetic studies including alternating field and thermal demagnetizations reveal that the swarm can be divided into two groups: group 1 has a characteristic magnetization of D = 296.6°, I = 82.2° with α 95 = 5.8° for N = 14 dikes with the corresponding pole position at 53.9°N, 77.4°W (δp, δm = 11.0°, 11.3°; group 2 has a characteristic magnetization of D = 157.6°, I = 53.9° with α 95 = 9.0° for N = 5 dikes with the corresponding pole position at 3.9°S, 35.5°W (δp, δm = 8.8°, 12.6°). One dike's magnetization was found to be reversed relative to the other group 2 dikes. Various magnetic experiments (low- and high-field hysteresis, Curie temperatures, susceptibility variation with temperature, coercivity of remanence, Lowrie–Fuller test) conducted to study the bulk magnetic and remanent magnetic properties of the dike material suggest that their behavior is consistent with multidomain pure magnetite being the dominant magnetic mineral. The group 1 pole position lies close to Newfoundland and is similar to other poles of equivalent age for intrusives from New Brunswick and Newfoundland. Rock units from the southeastern margin of the Iapetus Ocean thus seem to be yielding consistent "high-latitude" poles, a factor that needs to be taken into account in any discussion of the tectonic evolution of the area.